Improving the energy performance of historic buildings through their local features - Enrico Genova (Agathón)
This paper describes a methodology aimed to develop, for specific local contexts, a general framework of knowledge useful to improve the energy and environmental performances of historic buildings, in a way compatible to the conservation of its material and aesthetic features. This approach consists in analysing the recurring characteristics of the local architectural heritage, from the scale of building components to the urban dimension. As highlighted by an application to the historic centre of Palermo, this method is useful for carrying out large-scale energy analyses, for developing regulations and financial strategies, for assessing the effectiveness and compatibility of energy upgrade measures.